Perspektif Al-Qur’an dalam upaya mengatasi masalah sampah di masyarakat - Junaid, Ahmad Hariri Junaid Hariri (Maliki Interdisciplinary Journal, 2025)
Particularly in Indonesia, waste is frequently a significant issue for the community. Waste issues are frequently caused by people's actions that show less regard for environmental sustainability and environmental protection. The primary causes of society's lack of concern for preserving environmental sustainability are the community's rising standard of living, the fact that many people are still uneducated about environmental preservation, and the general lack of knowledge about how to properly process waste in order to preserve the sustainability of the surrounding environment. One of the goals of writing this essay is to inform people about how to apply the principles of the Quran to daily life in order to create a clean environment from contamination from waste. The research methodology is a literature review approach, which involves first evaluating research papers and journals for use as study material while creating articles and methods with the values of the Quran relevant to the subject to be examined. The study's findings show a connection to the principles found in Surah Al-A'raf verse 56 and Surah Al-Baqarah verse 205 of the Quran, which forbid inflicting harm to the earth.